Fatty acids in common minke whale (Balaenoptera acutorostrata) blubber reflect the feeding area and food selection, but also high endogenous metabolism. Issue 3 (15th March 2016) - Meier, Sonnich; Falk-Petersen, Stig; Aage Gade-Sørensen, Lars; Greenacre, Michael; Haug, Tore; Lindstrøm, Ulf
ABSTRACT: The fatty acid (FA) composition has been analysed in the blubber of 56 minke whales caught during the Norwegian commercial whaling period in 2009–2011. Minke whales from four regions were sampled: the North Sea, Vesterålen, Spitsbergen/Bear Island and Finnmark. The FA profiles of the whale blubber have been compared with FA profiles of potential prey species to investigate if FA analysis can be used to predict the diet of minke whales and how the FA profiles of the blubber reflect the regional ecosystem in which the whales were caught. Clear differences in blubber FA profiles were found between minke whales from different areas, and the results of the present study show that FA analysis of the blubber can be used to indicate the whale's diet, but there appears to be a strong impact from metabolism on several FAs. The whale blubber FAs are separate from those of the prey by having relatively high levels of FAs likely to originate from endogenous metabolism, such as 18:1n9 (Δ9-desaturation of 18:0); chain shortening products of 22:1(n-11); 20:1(n-11) and 18:1(n-11); as well as 22:5(n-3), which is an elongation product of 20:5(n-3). High metabolic activity in the adipose tissue was also evident by the clear stratification of FA profiles found throughout the blubber layer. It is remarkable that the whale blubber has much lower levels of the long-chain PUFAs 20:5(n-3) and 22:6(n-3) than found in the prey organisms. It is likely that this results from selective partitioning of diet FAs between the storage lipids and membrane lipids.